Hybrid Combination of the Dragonfly and Firefly Algorithms with Parameter Adaptation using Type-2 Fuzzy Logic and its Comparison with Cuckoo Search - Valdez, Fevrier; M. Guajardo, Hector; Castillo, Oscar; Melin, Patricia; Cortes-Antonio, Prometeo (International Journal of Combinatorial Optimization Problems and Informatics, 2026)
This paper explores a hybrid approach combining the Dragonfly Algorithm (DA) and Firefly Algorithm (FA) to balance exploration and exploitation, avoiding local optima and refining solutions in promising areas. The hybrid achieved higher-quality solutions, faster convergence to optimal results, and adaptability to diverse optimization problems through complementary strategies. Additionally, the Cuckoo Search Algorithm (CS), known for its effectiveness in global optimization via random search and solution space exploitation, was integrated. To further enhance performance, Type-2 Fuzzy Logic was applied for parameter adaptation in the algorithms. Smart citations: https://scite.ai/reports/10.61467/2007.1558.2026.v17i2.872 Dimensions. Open Alex.